2013
DOI: 10.1113/jphysiol.2013.254649
|View full text |Cite
|
Sign up to set email alerts
|

ATP release and Ca2+ signalling by human bronchial epithelial cells following Alternaria aeroallergen exposure

Abstract: Key points• Exposure of human bronchial epithelial (HBE) cells to fungal aeroallergens derived from Alternaria alternata stimulates Ca 2+ -dependent and Ca 2+ -independent ATP release across the apical membrane.• The Ca 2+ -dependent component was blocked by inhibitors of both ATP uptake and transport of exocytotic vesicles to the plasma membrane.• Treatment with inhibitors that target cysteine proteases significantly blocked Ca 2+ -dependent ATP release evoked by Alternaria in normal HBE cells, but not in cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 36 publications
4
57
1
Order By: Relevance
“…Alternaria alternata elicits inflammation in the lower respiratory tract in part via the actions of its serine proteases, which ultimately result in induction of pro‐inflammatory cytokines and leucocyte recruitment; results from cell culture and ex vivo studies suggest that the mechanism may (or may not) involve targeting of protease‐activated receptor‐2 (PAR2) . The A. alternata filtrate in our studies cleaved a fluorescent‐tagged casein substrate in a dose‐dependent fashion, and that heat‐inactivation (95°C for 10 minutes) reduced proteolytic activity to background levels (Figure A).…”
Section: Resultsmentioning
confidence: 74%
“…Alternaria alternata elicits inflammation in the lower respiratory tract in part via the actions of its serine proteases, which ultimately result in induction of pro‐inflammatory cytokines and leucocyte recruitment; results from cell culture and ex vivo studies suggest that the mechanism may (or may not) involve targeting of protease‐activated receptor‐2 (PAR2) . The A. alternata filtrate in our studies cleaved a fluorescent‐tagged casein substrate in a dose‐dependent fashion, and that heat‐inactivation (95°C for 10 minutes) reduced proteolytic activity to background levels (Figure A).…”
Section: Resultsmentioning
confidence: 74%
“…We have previously shown that exposure of asthmatic patients to a single HDM administration via the airways leads to the release of ATP and uric acid in the bronchoalveolar lavage (Idzko et al, 2007;Kool et al, 2011). Although the exact cellular source of these DAMPs has not been formally identified in these patients, several reports show that ECs directly release ATP when stimulated by allergens like grass pollen or Alternaria alternata (O'Grady et al, 2013). In mice, a single exposure to HDM is sufficient to trigger uric acid (UA) production by airway ECs (Kool et al, 2011), which is crucial in boosting the production of HDMinduced TSLP, GM-CSF, IL-25, and IL-33.…”
Section: Epithelial-derived Damps and Alarmins Promote Th2-cell-mediamentioning
confidence: 98%
“…Airway epithelium appears to be first to be affected by Alt exposure. Several studies, primarily using cell line models, have found various Alt-induced epithelial responses, such as cytokine transcription (13,14), secretion (15), ATP release (16), and calcium flux (15)(16)(17).…”
mentioning
confidence: 99%